2017
DOI: 10.7812/tpp/16-122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Longitudinal Electronic Health Record Training for Residents Preparing for Practice in Patient-Centered Medical Homes

Abstract: Comprehensive training designed to improve EHR competencies among residents practicing in a PCMH resulted in improved assessment scores. Our findings indicate EHR training as part of resident exposure to the PCMH measurably improves self-assessed competencies, even among residents less engaged in EHR training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…This finding was consistent with a qualitative study conducted in two London‐based hospitals, in which it was reported that the lack of basic typing skills was one of the factors that contributed to workarounds to the EHR in mental health hospitals . Previous studies have shown that training improves the self‐assessment of competency in the use of the EHR system . Hence, in addition to high‐quality and continuous HIS training, it is highly recommended that health care organizations provide training in typing skills, especially to senior doctors, in an effort to improve their proficiency in using the HIS.…”
Section: Discussionsupporting
confidence: 85%
“…This finding was consistent with a qualitative study conducted in two London‐based hospitals, in which it was reported that the lack of basic typing skills was one of the factors that contributed to workarounds to the EHR in mental health hospitals . Previous studies have shown that training improves the self‐assessment of competency in the use of the EHR system . Hence, in addition to high‐quality and continuous HIS training, it is highly recommended that health care organizations provide training in typing skills, especially to senior doctors, in an effort to improve their proficiency in using the HIS.…”
Section: Discussionsupporting
confidence: 85%
“…EHR training is often provided in a limited number of sessions as an onboarding component. However, advanced longitudinal training and support of clinical staff improves self-assessment of competency [48,49].…”
Section: Recommendationsmentioning
confidence: 99%
“…Known barriers and facilitators to HIT adoption, in general, may also be impactful for HIT targeting cancer screening. For example, evidence indicates that barriers to HIT use include inadequate training for care teams on using EHR functions to their full potential [ 55 - 58 ]. Thus, effective implementation strategies for HIT targeting cancer prevention may involve training.…”
Section: Discussionmentioning
confidence: 99%